Natural environment ethics, law and environmental policies: an attempt for balance and perspectives for the future - Bondolfi, Alberto (Acta Bioethica, 2001)
Upon the last three decades an articulate reflection on the good and fair relationship man have to maintain with the natural environment that surrounds him has been developed in different cultural settings. This reflection has been constructed differently, according with the dfferent options and schools of thought that characterize the ethical argument related to environmental matters. This paper presents and examines that reflection trying to clearly identify internal conextions and eventual differences among distinct trends.